MEDIA PEMBELAJARAN MOBILE LEARNING UNTUK MENINGKATKAN MOTIVASI DAN KEMAMPUAN PRAKTIKUM MAHASISWA STIKES KARSA HUSADA GARUT - Erlinawati, N. Ai; Suherman, Uman; Darmawan, Deni (PEDAGOGIA, 2016)
Appropriate learning media do not support this lack of motivation to learn and the ability of students in the biology lab suspected in addition to the abstract nature of the study, as well as lectures. This research will study whether use of m-Learning  Mobile learning can increase learning motivation and the ability of student practicum STIKes Karsa Husada on the function and cells animal and plant?. The study was conducted and using a   quantitative approach with a   purely experimental method. This  Biology (Cell and Function in  Animals and  Plants)  using  Mobile-Learning  Media can improve student practicum, good skills preparation tool and material, work MFI, make preparations, observation preparations, identifying the cell, as well as skills distinguishing cell organelles. The results of these studies recommended to the faculty; it would be better if the Mobile learning is also used to deliver other materials. Because by using this method, the students are not only enthusiastic (motivated) to interact in lectures but also able to increase their works. Some other mediums of learning, besides Mobile-Learning, it suggested for the next researchers that they can examine the various advantages and accuracy of each medium of learning from the aspects of the lecture material. Keywords: Mobile-Learning, Motivation, Practicum